2017
DOI: 10.1128/iai.00985-16
|View full text |Cite
|
Sign up to set email alerts
|

Perforin Expression by CD8 T Cells Is Sufficient To Cause Fatal Brain Edema during Experimental Cerebral Malaria

Abstract: Human cerebral malaria (HCM) is a serious complication of Plasmodium falciparum infection. The most severe outcomes for patients include coma, permanent neurological deficits, and death. Recently, a large-scale magnetic resonance imaging (MRI) study in humans identified brain swelling as the most prominent predictor of fatal HCM. Therefore, in this study, we sought to define the mechanism controlling brain edema through the use of the murine experimental cerebral malaria (ECM) model. Specifically, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 49 publications
4
51
0
Order By: Relevance
“…The reduction in claudin-5 contributes to an increased permeability of BBB during the progression of CM [7]. Our results provide further evidence that mRNA and protein levels of claudin-5 are reduced in in vivo and in vitro models of mouse ECM.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The reduction in claudin-5 contributes to an increased permeability of BBB during the progression of CM [7]. Our results provide further evidence that mRNA and protein levels of claudin-5 are reduced in in vivo and in vitro models of mouse ECM.…”
Section: Discussionsupporting
confidence: 67%
“…An elevated intracranial hypertension was observed in 75–80% of African children with CM, who either died or survived with neurological sequelae . The high intracranial pressure in CM is partially caused by increased vascular permeability and brain edema . During progression of CM, accumulation of infected red blood cells (iRBCs) and immune cells in cerebral vessels induces malfunction of the blood–brain barrier (BBB) , leading to a fatal outcome .…”
mentioning
confidence: 99%
“…In vivo in mice it was shown that parasite-specific CD8 + T cells interact with endothelial cells in an interferon-gamma (IFN-γ ) dependent manner, and that this was responsible for activating endothelial cells in the brain microvasculature (Swanson et al, 2016). Moreover, CD8 + T cells expressing perforin were responsible for vascular permeability breakdown inducing brain swelling and oedema (Huggins et al, 2017). Therefore, although cerebral malaria is primarily a problem of a disrupted blood supply to the brain, the CNS can be affected in a broader sense and is likely to be protected by its defense machinery, including the microglia.…”
Section: (A) Plasmodium Falciparummentioning
confidence: 99%
“…Next, we assessed thymi during TMEV infection in C57BL/6 mice. C57BL/6 mice clear TMEV infection within 21-45 days post infection (15,16,20,48). Because C57BL/6 mice mount an effective antiviral CD8 T cell response, this model allows us to determine whether thymic involution is reversible upon viral clearance (20,74).…”
Section: Thymic Involution Following Acute Neurological Injuries Is Rmentioning
confidence: 99%